2015
DOI: 10.1369/0022155415576540
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of p16, Ki67 and COX-2 Is Associated with Basal Phenotype in High-Grade Ductal Carcinoma In Situ of the Breast

Abstract: + /COX2-co-expression showed significant associations with the basal phenotype and these profiles could be used to guide more aggressive treatment strategies in patients with high-grade DCIS. (J Histochem Cytochem 63:408-416, 2015) Keywords biological markers, biomarkers, breast cancer, ductal carcinoma in situ p16,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Therefore, it may be hypothesized that COX-2 has potential as a prognostic biomarker for breast cancer. Previous studies have reported that COX-2 was upregulated and associated with tumor invasiveness and clinical outcome in numerous types of human cancer (27)(28)(29)(30). In the present study, a correlation was revealed between high COX-2 expression and poor differentiation status (P<0.05).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, it may be hypothesized that COX-2 has potential as a prognostic biomarker for breast cancer. Previous studies have reported that COX-2 was upregulated and associated with tumor invasiveness and clinical outcome in numerous types of human cancer (27)(28)(29)(30). In the present study, a correlation was revealed between high COX-2 expression and poor differentiation status (P<0.05).…”
Section: Discussionsupporting
confidence: 68%
“…Previous reports showed that p16 is over‐expressed in basal breast carcinoma (Perez et al . ). Although MDA‐MB‐231 is derived from adenocarcinoma, the aggressive phenotype of this type of breast cancer cells can be attenuated by miR‐340 over‐expression followed by p16 decline.…”
Section: Discussionmentioning
confidence: 97%
“…The treatment of ductal carcinoma in situ remains a challenge as the clinicopathologic features of the disease do not reliably stratify patients into distinct risk groups to guide treatment decision [23]. For this reason, some studies have attempted to risk stratify ductal carcinoma in situ based on genetic and molecular factors, including Oncotype Dx ® ductal carcinoma in situ score [24][25][26][27][28]. Although ductal Fig.…”
Section: Discussionmentioning
confidence: 99%